2019
DOI: 10.3389/fonc.2019.00171
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal Pathways and Autophagy Distinctively Control Endothelial Cell Behavior to Affect Tumor Vasculature

Abstract: Cancer cell-stromal cell crosstalk is orchestrated by a plethora of ligand-receptor interactions generating a tumor microenvironment (TME) which favors tumor growth. The high pro-angiogenic nature of the TME perpetuates the chaotic network of structurally immature, low pericyte-covered vessels characteristic of the tumor vasculature. We previously demonstrated that chloroquine (CQ) -a lysosomotropic agent used as first-generation autophagy blocker in clinical trials- induced tumor vessel normalization and redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 40 publications
(63 reference statements)
0
16
0
Order By: Relevance
“…found that lysosomal inhibition by CQ impaired de novo nucleotide biosynthesis and depleted aspartate in pancreatic ductal adenocarcinoma 24 . Even the aforementioned vessel-normalizing ability of CQ was proposed in a recent study to be related to lysosomal dysfunction 25 .…”
Section: Discussionmentioning
confidence: 99%
“…found that lysosomal inhibition by CQ impaired de novo nucleotide biosynthesis and depleted aspartate in pancreatic ductal adenocarcinoma 24 . Even the aforementioned vessel-normalizing ability of CQ was proposed in a recent study to be related to lysosomal dysfunction 25 .…”
Section: Discussionmentioning
confidence: 99%
“…***p < 0.001 groups showed the completion of autophagic response after the exposure to the Met, while the current results showed contradictory P62 changes after autophagy modulation in progenitor cells oriented toward endothelial lineage. One reason for this discrepancy would be that the treatment of cells with lineage-specific factors could alter or blunt the normal function of the autophagic signaling pathway effector [30]. Therefore, one could hypothesize that the treatment of human bone marrow CD146 + cells could alter cellular levels of main autophagic regulators such as Beclin-1, P62, and LC3II/I ratio.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that Vav1 is transported to lysosomes by another carrier protein, VEGFR1, in endothelial cells. VEGFR1 is a receptor tyrosine kinase molecule that is known to be degraded by lysosomal proteolysis [27]. Vav1 binds at the binding motif of Y-K-E-P to VEGFR1, and knockdown of VEGFR1 inhibits Vav1 degradation, and conversely activation of VEGFR1 increases Vav1 degradation.…”
Section: Discussionmentioning
confidence: 99%